Series of highly stable Cd(ii)-based MOFs as sensitive and selective sensors for detection of nitrofuran antibiotic. Issue 46 (26th October 2021) - Zhou, Shanhe; Lu, Lu; Liu, Dong; Wang, Jun; Sakiyama, Hiroshi; Muddassir, Mohd.; Nezamzadeh-Ejhieh, Alireza; Liu, Jianqiang
Abstract : The oxygen atom of the MOF ether-bridging group acts as a Lewis base site, improving the connection and allowing the detection of 10 antibiotics through the fluorescence quenching effect. Abstract : The abuse of antibiotics has caused global problems including critical environmental ecology impacts. Herein, four new metal–organic frameworks (MOFs) – [Cd(HL)(bic)(H2 O)]·2H2 O(1 ), [Cd3 (L)2 (bbi)2 (H2 O)2 ]·2H2 O(2 ), [Cd3 (L)2 (bib)2 (H2 O)2 ] (3 ) and [Cd3 (L)2 (idy)2 ] (4 ), where bic = 3, 6-bis(imidazol-1-yl)-9 H -carbazole, bbi = 1, 1′-(1, 4-butanediyl)bis(imidazole), bib =1, 4-bis(1-imidazoly)benzene and idy = 2-imidazol-1-ylpyridine – have been synthesized and fully characterized. 1 is a 1D chain with a large loop, stacked parallel to each other in 2D supramolecular layers by hydrogen-bonded and packing interactions. 2 and 3 are isostructural and show a 3D (3, 8)-connected tfz -type network with (4 3 )2 (4 6 ·6 18 ·8 4 ) topology. 4 has a 2D grid framework. The oxygen atom of the ether-bridging group acts as a Lewis base site, which improves the connection strength and allows the detection of 11 types of antibiotics through the fluorescence quenching effect. Among them, 2 exhibits sensitive and selective detection for nitrofural (NZF) ( K SV = 8.26 × 10 3 M −1 and LOD = 1.83 ppm). Moreover, the highly selective probe behavior towards NZF ions could be maintained even if there are other interfering antibiotics.